ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI - Wisnu Budhi Prasetya, Alwi Suddin & Sumarno Dwi Saputra (Universitas Slamet Riyadi, 2017)
In this globalization era culinary sector of business grow with very quickly andprovide an effort to compete in every products or services marketing activity. Everymarketing activity has a very important role in business activity, remember theorientation of marketing activity is to providing value to the consumer. Every business ineach business category is required to have sensitivity to any changes thatoccur.Nowadays, eating and drinking in the restaurant has become a habit of Indonesianpeople, especially for the youth generation who wanting to be exist and avowed in hissocial circle, not eating and drinking only, but the restaurant also become a destinationfor their activities, such as watching football together, meeting up with their friends orcolleagues or just to hanging out. Grow and increase of business in this culinary sectormake the business are challenged to be more competitive in this dynamic competitionand will lead every business owner to observe the competition in their business circle. Toface the competition, every companies are required to optimize their human resources toincrease competitiveness, optimize effectiveness and develop their marketing strategiesconstantly and continuously. This should be done by the doer as an effort to gain acompetition to against their competitors. By improving the 1) quality service so that 2)customer satisfaction is met so as to create 3) customer loyalty.Keywords: service quality, quality loyalty, customer satisfactionPENDAHULUANSemakin marak dengan banyaknya restoranbaru yang berdiri dan tersebar di wilayahsolo, namun tidak semua restoran di Solobanyak dikunjungi oleh konsumen, karena hanyarestoran tertentu yang terlihat ramai pengunjung.Kualitas pelayanan yang dilakukanoleh restoran harus dijaga untuk dapat bertahandalam persaingan yang ketat. Hal tersebutmutlak dilakukan oleh pemilik usaha yang sedangdikelola. Jika sebuah usaha akan bertahanhidup, maka haruslah memikirkan cara efektifagar dapat bersaing. Salah satu cara adalahdengan meningkatkan kualitas pelayanan.Kualitas pelayanan memiliki hubunganyang erat dengan kepuasan pelanggan.